Synthesis, biological evaluation and molecular docking study of some novel indole and pyridine based 1, 3, 4-oxadiazole derivatives as potential antitubercular agents. Issue 7 (1st April 2016) - Desai, N.C.; Somani, Hardik; Trivedi, Amit; Bhatt, Kandarp; Nawale, Laxman; Khedkar, Vijay M.; Jha, Prakash C.; Sarkar, Dhiman
Graphical abstract: Abstract: A series of indole and pyridine based 1, 3, 4-oxadiazole derivatives5a –t were synthesized and evaluated for their in vitro antitubercular activity against Mycobacterium tuberculosis H37 Ra (MTB) and Mycobacterium bovis BCG both in active and dormant state. Compounds5b, 5e, 5g and5q exhibited very good antitubercular activity. All the newly synthesized compounds5a –t were further evaluated for anti-proliferative activity against HeLa, A549 and PANC-1 cell lines using modified MTT assay and found to be noncytotoxic. On the basis of cytotoxicity and MIC values against Mycobacterium bovis BCG, selectivity index (SI) of most active compounds5b, 5e, 5g and5q was calculated (SI = GI50 /MIC) in active and dormant state. Compounds5b, 5e and5g demonstrated SI values ⩾10 against all three cell lines and were found to safe for advance screening. Compounds5a –t were further screened for their antibacterial activity against four bacteria strains to assess their selectivity towards MTB. In addition, the molecular docking studies revealed the binding modes of these compounds in active site of enoyl reductase (InhA), which in turn helped to establish a structural basis of inhibition of mycobacteria. The potency, low cytotoxicity and selectivity of these compounds make them valid lead compounds for further optimization.